(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Description and analysis of creation procedures and scenic-narrative language by Núcleo Carioca de Teatro in the productions of Correio sentimental de Nelson Rodrigues (1999) and A prosa do Nelson (2000), by Nelson Rodrigues, in which the author was as performer, body trainer and researcher.